2017
DOI: 10.1016/j.tplants.2016.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Commandeering Channel Voltage Sensors for Secretion, Cell Turgor, and Volume Control

Abstract: Control of cell volume and osmolarity is central to cellular homeostasis in all eukaryotes. It lies at the heart of the century-old problem of how plants regulate turgor, mineral and water transport. Plants use strongly electrogenic H+-ATPases, and the substantial membrane voltages they foster, to drive solute accumulation and generate turgor pressure for cell expansion. Vesicle traffic adds membrane surface and contributes to wall remodelling as the cell grows. Although a balance between vesicle traffic and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
70
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 107 publications
0
70
0
Order By: Relevance
“…Previous work showed that the SYP121 interacts with KAT1 and the closely related KC1 channel subunits in vitro (Honsbein et al, ; Honsbein et al, ), and binding with KC1 in roots was essential for channel mediated K + uptake in vivo and growth (Honsbein et al, ). These and additional studies isolated the binding motifs to the N‐terminal F 9 xRF motif of SYP121 and the RYxxWE motif immediately preceding the first transmembrane α‐helices of the K + channels (Grefen et al, ; Grefen, Chen, et al, ; Karnik et al, ). Although SNARE‐channel binding promotes vesicle traffic as well as channel‐mediated K + influx, how these two, physiologically distinct processes might be temporally coordinated has remained obscure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous work showed that the SYP121 interacts with KAT1 and the closely related KC1 channel subunits in vitro (Honsbein et al, ; Honsbein et al, ), and binding with KC1 in roots was essential for channel mediated K + uptake in vivo and growth (Honsbein et al, ). These and additional studies isolated the binding motifs to the N‐terminal F 9 xRF motif of SYP121 and the RYxxWE motif immediately preceding the first transmembrane α‐helices of the K + channels (Grefen et al, ; Grefen, Chen, et al, ; Karnik et al, ). Although SNARE‐channel binding promotes vesicle traffic as well as channel‐mediated K + influx, how these two, physiologically distinct processes might be temporally coordinated has remained obscure.…”
Section: Discussionmentioning
confidence: 99%
“…Although we note some quantitative differences, the overall effect of SYP121 on the macroscopic KAT1 current is qualitatively similar. Like the KC1 channel, SYP121 action also depended on the conserved RYxxWE motif at the cytosolic face of the VSD (Grefen et al, ; Karnik et al, ), and mutation of Trp 62 in KAT1 was sufficient to eliminate the effects of SYP121 on KAT1 gating (Figure a). Heterologous function of the KC1‐AKT1 assembly requires CBL‐dependent kinase expression in oocytes (Honsbein et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SYP121 also binds with the K + channels KC1 and KAT1, altering channel gating to promote K + uptake and conferring a voltage dependence to secretory traffic for growth (Honsbein et al, 2009Grefen et al, 2010Grefen et al, , 2015. Binding with SYP121 has been shown to promote vesicle traffic with osmotic solute uptake, including that of K + , effectively coordinating the two processes and maintaining turgor as the cell expands (Karnik et al, 2017).…”
mentioning
confidence: 99%